Cross-national prevalence and factors associated with suicide ideation and attempts in older and young-and-middle age people. (1st September 2020) - Cabello, Maria; Miret, Marta; Ayuso-Mateos, José Luis; Caballero, Felix Feliz; Chatterji, Somnath; Tobiasz-Adamczyk, Beata; Haro, Josep Maria; Koskinen, Seppo; Leonardi, Matilde; Borges, Guilherme
Abstract: Objectives: To report prevalence estimates of 12-month suicide ideation and attempts in young-and-middle age adults and older people, as well as their respective associated factors. Methods: A total of 52, 150 community-dwelling adults who completed the adapted version of the Composite International Diagnostic Interview-Depression Module were included from SAGE and COURAGE in Europe studies. The presence of 12-month suicide ideation and attempts was measured among the participants who screened positively in the Depression Module. Global and national prevalence estimates of 12-month suicide ideation and attempts were calculated according to the total sample. Logistic regression analyses were conducted to separately determine factors associated with suicidal ideation and with suicide attempts in young-and-middle age adults and older adults. Results: Higher estimates of 12-month suicidal ideation were found for high-income countries and people aged 65 years and older. Higher negative affect, higher disability, and presence of food insecurity were associated with 12-month suicidal ideation and suicide attempts for young-and-middle-adults and older adults. Higher isolation, being female, and greater number of chronic health conditions were also related to 12-month suicidal ideation in both age groups. Younger age was associated with 12-month suicidal ideation for older people, and with suicide attempts in the young-and-middle age group. Finally, higher income was related to lower rates of 12-month suicidal ideation for the young-and-middle age group. Conclusions: Older people are at increased risk of suicidal ideation globally and of suicide attempts in some countries. There were common and different factors related to suicide in adults and older adults.